2017
DOI: 10.1186/s12887-017-0781-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel, putatively null, FGD1 variant leading to Aarskog-Scott syndrome in a family from UAE

Abstract: BackgroundThe X-linked condition “Aarskog-Scott syndrome (AAS)” causes a characteristic combination of short stature, facial, genital and skeletal anomalies. Studies elucidated a causative link between AAS and mutations in the FGD1 gene, which encodes a Rho/Rac guanine exchange factor. FGD1 is involved in regulating signaling pathways that control cytoskeleton organization and embryogenesis.Case presentationFGD1 was studied in an Emirati family with two cases of AAS using PCR amplification and direct sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Intriguingly, his mother and sister also carried the same FGD1 variant, who only presented with mild short stature. This was also observed in other female carriers ( 2 , 17 , 30 ). Alternatively, clinical phenotypes of female patients with AAS, in general, seemed relatively mild, which may be associated with X chromosome inactivation ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Intriguingly, his mother and sister also carried the same FGD1 variant, who only presented with mild short stature. This was also observed in other female carriers ( 2 , 17 , 30 ). Alternatively, clinical phenotypes of female patients with AAS, in general, seemed relatively mild, which may be associated with X chromosome inactivation ( 31 , 32 ).…”
Section: Discussionsupporting
confidence: 79%
“…Children with AAS have heterogeneous clinical manifestations. Short stature, craniofacial, genital, and skeletal anomalies are the classically characteristic combination ( 2 ). With respect to short stature, the most common symptom in the disease; it is disproportionate, with an increased upper-to-lower segment ratio and shortened distal extremities ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The guanine nucleotide exchange factor FGD1 could activate Rho GTPase cell division cycle 42. Reports showed that FGD1 was a critical gene marker to the diagnosis of Aarskog‐Scott syndrome (Griffin, Farley, Antonellis, & Keegan, ; Hamzeh et al, ) and breast cancer (Beasley, Buckhaults, Pedigo, & Farrell, ), implying its important role in the development of cancer. Collectively, these genes we found in our study might play an important role in the development of HCC.…”
Section: Discussionmentioning
confidence: 99%